2017
DOI: 10.1039/c7dt03003g
|View full text |Cite
|
Sign up to set email alerts
|

Two-step hydrothermally synthesized carbon nanodots/WO3 photocatalysts with enhanced photocatalytic performance

Abstract: In this study, carbon nanodots (C-dots)/WO photocatalysts were prepared via a two-step hydrothermal method. The morphologies and optical properties of the as-prepared materials were investigated. Compared with the prepared WO and C-dots, the C-dots/WO possessed stronger photocatalytic capability and excellent recyclability for photocatalytic elimination of Rhodamine B. For example, the achieved first order reaction rate constant of 0.01942 min for C-dots/WO was ∼7.7 times higher than that of the prepared WO. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(83 citation statements)
references
References 40 publications
1
82
0
Order By: Relevance
“…They found that color removal reached 52–77% from the waste oil and the best adsorbent was acid activated clay. The other promising technique for color removal is a photocatalytic reaction . Zhang et al reported that the hetero‐structured TiO 2 /SnO 2 nanofibers exhibited a much higher degradation rate of methylene blue, rhodamine B, and 4‐chlorophenol in photocatalytic test, while Song et al found that C‐dots/WO 3 possessed stronger photocatalytic capability and excellent recyclability for photocatalytic elimination of Rhodamine B.…”
Section: Waste Lube Oils Processing Technologiesmentioning
confidence: 99%
“…They found that color removal reached 52–77% from the waste oil and the best adsorbent was acid activated clay. The other promising technique for color removal is a photocatalytic reaction . Zhang et al reported that the hetero‐structured TiO 2 /SnO 2 nanofibers exhibited a much higher degradation rate of methylene blue, rhodamine B, and 4‐chlorophenol in photocatalytic test, while Song et al found that C‐dots/WO 3 possessed stronger photocatalytic capability and excellent recyclability for photocatalytic elimination of Rhodamine B.…”
Section: Waste Lube Oils Processing Technologiesmentioning
confidence: 99%
“…It has been reported in previous works that lower‐valence cations and O 2− vacancies could form in the crystal structure after Ti 2 Nb 2x O 4+5x based oxides being calcined in N 2 atmosphere, leading to the generation of nonstoichiometric oxides Herein, the TiNb 2 O 7 (TNO) in the TNO/CNT‐KB composite should be expressed as the nonstoichiometric Ti 4 Nb 8 O 29‐1‐ x ( x >0) containing a certain amount of lower‐valence cations and O 2− vacancies, which is isostructural to Ti 2 Nb 10 O 29 . It can be seen from the Ti 2p 3/2 XPS spectra of TNO and TNO/CNT‐KB samples (Figure S2a and 2b, Supporting Information) that TNO/CNT‐KB sample contains more Ti 3+ ions than TNO sample.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported in previous works that lowervalence cations and O 2À vacancies could form in the crystal structure after Ti 2 Nb 2x O 4 + 5x based oxides being calcined in N 2 atmosphere, leading to the generation of nonstoichiometric oxides. [14,21À 23] [14,[21][22][23][24] It can be seen from the Ti 2p 3/2 XPS spectra of TNO and TNO/CNT-KB samples ( Figure S2a and 2b, Supporting Information) that TNO/CNT-KB sample contains more Ti 3 + ions than TNO sample. Besides, the two samples show the broad diffraction peaks in the XRD patterns, especially for the TNO/ CNT-KB, indicating small grain sizes of the materials.…”
Section: Physical Characterizationmentioning
confidence: 99%
“…[52][53][54][55][56] Currently,t he main focus of research is on how to improve their captureability and selectivity for CO 2 . [52][53][54][55][56] Currently,t he main focus of research is on how to improve their captureability and selectivity for CO 2 .…”
Section: Solid-waste-derived Carbon-based Co 2 Adsorbentsmentioning
confidence: 99%